2018
DOI: 10.1016/j.jfineco.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

The buyers’ perspective on security design: Hedge funds and convertible bond call provisions

Abstract: We provide evidence that security design reflects the interplay of capital supplier and security issuer preferences. While call provisions have historically been the default option in convertible security design, only a minority of post-2005 issues are callable. Because hedge funds dominate the market for new convertibles today and because convertible arbitrage is less risky without callability, the recent diminution in the frequency of call provisions in new convertible bond issues illustrates the importance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 63 publications
1
16
0
Order By: Relevance
“…Our study provides new insights into the importance of the buy-side of the convertible bond market. We hypothesize that firms set shorter maturities because many recently issued convertibles are not embedded with call provisions, which satisfies arbitrageurs' preferences (Grundy and Verwijmeren, 2018). 2 Robbins and Schatzberg (1986) show that long-term callable bonds and short-term non-callable bonds can be substitutes under certain market conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Our study provides new insights into the importance of the buy-side of the convertible bond market. We hypothesize that firms set shorter maturities because many recently issued convertibles are not embedded with call provisions, which satisfies arbitrageurs' preferences (Grundy and Verwijmeren, 2018). 2 Robbins and Schatzberg (1986) show that long-term callable bonds and short-term non-callable bonds can be substitutes under certain market conditions.…”
Section: Introductionmentioning
confidence: 99%
“…By observing the distribution of the bond issuance years, we also find that noncallable convertible bonds become more popular than callable convertibles starting in 2005. This echoes Grundy and Verwijmeren's (2018) observation, for they argue that the presence of call provisions could increase the risk for convertible arbitrageurs, the dominant investors in the convertible bond market.…”
Section: Empirical Evidencementioning
confidence: 55%
“…A detailed review of convertible bond pricing models can be found in Batten et al (2014), Kwok (2014), and Batten et al (2018). 5 According to data collected by Grundy and Verwijmeren (2018), a majority of convertible bonds issued before 2000 are callable; noncallable convertible issues became popular after 2003. In addition, according to the statistics recorded in Finnerty (2015), about 49.44% of investment-grade, 84.44% of speculative-grade, and 68.99% of nonrated callable convertibles are putable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…design (Grundy and Verwijmeren, 2018). To our knowledge, there is no prior survey evidence on the role of the supply side of capital in capital structure decisions.…”
Section: Capital Supply Factorsmentioning
confidence: 97%